Psychological Well-Being dan Celebrity Worship (Intense-Personal) Penggemar K-Pop - Wijaya, Patricia Putri; Rahayu, Maria Nugraheni Mardi (Universitas Darul Ulum, 2025)
This study aims to determine the relationship between psychological well-being (PWB) and celebrity worship (intense-personal) (IPCW) in Gen Z K-Pop fans in Java. The participants in this study were 289 Gen Z K-Pop fans in Java Island consisting of 262 women (90.7%) and 27 men (9.3%). Data collection was done through accidental sampling. The research method used was quantitative research method with correlational design. The measurement scale used CAS (α=0.85) and RPWBS (α=0.912). The results of the correlation analysis show that PWB and IPCW have a significant negative relationship in the dimensions of autonomy, environmental mastery, personal growth, life goals, and self-acceptance. While PWB in the dimension of positive relationships with others has no significant relationship with IPCW. For this reason, K-Pop fans need to pay attention to their psychological well-being so that they are not trapped in IPCW behavior.